2023
DOI: 10.3390/brainsci13030514
|View full text |Cite
|
Sign up to set email alerts
|

Altered Postcentral Connectivity after Sleep Deprivation Correlates to Impaired Risk Perception: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Background: Previous studies revealed that sleep deprivation (SD) impairs risk perception and leads to poor decision-making efficiency. However, how risk perception is related to brain regions’ communication after SD has not been elucidated. In this study, we investigated the neuropsychological mechanisms of SD-impaired risk perception. Methods: Nineteen healthy male adults were recruited and underwent resting-state functional magnetic resonance imaging during a state of rested wakefulness and after nearly 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In 24 studies, two or three time sessions of 6–16 min duration were offered, and so the number of trials depended on the speed of the participants’ response. The number of trials was predetermined in 13 studies ( Chiu et al, 2012 ; Pletzer et al, 2016 ; McCormick and Telzer, 2017a , b ; Hoffmann et al, 2018 ; Rao et al, 2018 ; Gentili et al, 2020 ; Ji S. et al, 2021 ; Jorge et al, 2022 ; Poudel et al, 2022 ; Chen et al, 2023 ; Hu et al, 2023 ; Leota et al, 2023 ). One study used a small predetermined time, composed of four cycles of 30 s to pump an unlimited number of balloons ( Lee et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 24 studies, two or three time sessions of 6–16 min duration were offered, and so the number of trials depended on the speed of the participants’ response. The number of trials was predetermined in 13 studies ( Chiu et al, 2012 ; Pletzer et al, 2016 ; McCormick and Telzer, 2017a , b ; Hoffmann et al, 2018 ; Rao et al, 2018 ; Gentili et al, 2020 ; Ji S. et al, 2021 ; Jorge et al, 2022 ; Poudel et al, 2022 ; Chen et al, 2023 ; Hu et al, 2023 ; Leota et al, 2023 ). One study used a small predetermined time, composed of four cycles of 30 s to pump an unlimited number of balloons ( Lee et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…The major difference between the current and previous experimental studies is in the mental stress of subjects and workload during TSD. Previous research in laboratory conditions has revealed increased rs-fMRI features (ALFF, ReHo) in the postcentral and temporal gyrus after sleep deprivation ( Chen et al, 2023 ; Li et al, 2023 ). In their study, Chen et al (2023) reported an increase of ReHo in the right postcentral gyrus after sleep deprivation, which is consistent with observations in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in laboratory conditions has revealed increased rs-fMRI features (ALFF, ReHo) in the postcentral and temporal gyrus after sleep deprivation ( Chen et al, 2023 ; Li et al, 2023 ). In their study, Chen et al (2023) reported an increase of ReHo in the right postcentral gyrus after sleep deprivation, which is consistent with observations in the present research. However, we also detected increased rs-fMRI features in other brain regions after sleep deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced functional connectivities within the somatosensory network were associated with poorer sleep quality ( Bai et al, 2022 ). A recent within-subject study showed significantly higher regional homogeneity of rPoCG following 36 h of sleep deprivation, as compared to a state without sleep deprivation ( Chen et al, 2023 ). According to a model of insomnia ( Riemann et al, 2010 ), higher connectivity between the hypothalamus and rPoCG in smokers may reflect a hyperarousal state, whereby excessive somatosensory information processing leads to deficient sleep ( Scammell et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%